Nanotwinned Structure-Dependent Photocatalytic Performances of the Multipod Frameworks of Cu7S4 Hollow Microcages - Zhang, Hongdan; Xuan, Yang; Cheng, Peng; Ma, Wenwen; Zhao, Zhen; Liu, Xiaoyang (Frontiers in Chemistry, 2020)
The 14-pods Cu7S4 hollow microcages wholly exposed with nanotwinned building blocks were successfully prepared by an ethanol-assisted sacrificial Cu2O template approach. Its photocatalytic activity for the degradation of methylene blue (MB) was determined. The results suggest that the Cu7S4 microcages with nanotwinned building blocks possess higher catalytic activity than the Cu7S4 microcages without the nanotwinned structures, suggesting that the special nanotwinned components can improve the catalytic performance of the multipod framework. Further investigate reveals that the nanotwins inside the Cu7S4 microcages can facilite the transport of free charges, decrease the recombination of photoinduced electrons and holes, and elongate the lifetime of the electron–hole pairs. Our work will provide a powerful evidence that the nanotwinned building blocks of the synthesized Cu7S4 microcages play a crucial role for the high catalytic activity.